Pembuatan Cake Tepung Ubi Jalar Ungu Dengan Penambahan Pure Buah Nangka Terhadap Nilai Antioksidan, Karakteristik Kimia dan Organoleptik - Elly Mita; Alfi Nur Rochmah (Universitas Veteran Bangun Nusantara, 2023)
Cake is a snack with a sweet taste that uses a mixture of three main ingredients, namely wheat flour, eggs and sugar. The addition of jackfruit puree has a distinctive aroma, taste and antioxidant potential so it can be used as a composition ingredient in making purple sweet potato flour cake. This research aims to determine the antioxidant value, chemical and organoleptic characteristics of purple sweet potato flour cake. The samples used in making purple sweet potato flour cake with the addition of jackfruit puree were without adding jackfruit puree (control), adding 20% jackfruit puree from the total flour use, adding 30% jackfruit puree from the total flour use and adding 40% jackfruit puree from the total use of flour. Based on the organoleptic results, the SPSS version 23 test and the De Garmo test of the selected samples, namely the formulation of adding 30% jackfruit puree from the total flour used, then chemical analysis was carried out including water content, ash content, protein content, fat content, carbohydrate content and antioxidant value. The results of chemical analysis of selected samples showed a water content of 32.76%, ash content of 1.33%, protein content of 4.76%, fat content of 18.45%, carbohydrate content of 42.7% and antioxidant value of 21.6%. Keywords: Cake, Purple Sweet Potato Flour, Jackfruit Puree